Study on the influence mechanism of students’ behavior of participation in industrial colleges—Analysis framework based on theory of planned behavior - Zhang, Yuanbao; Shen, Xiangdong; Song, Jinyu; Huang, Tiantian (Frontiers in Psychology, 2022)
As a new organizational form for the coordinated development of education and industry, industrial college is an important carrier for application-oriented colleges and universities to implement application-oriented talent training. However, in the present time the enthusiasm and motivation of college students to participate in the study of industrial colleges are not high, which seriously affects the training quality of applied talents. The purpose of this study is to explore the main factors and their action mechanism affecting students' participation in industrial colleges. Taking Ajzen’s (2002) Theory of Planned Behavior (TPB) as the theoretical framework, this study constructs the influencing factor model of college students' participation in industrial college from five aspects: behavior attitude, subjective norms, perceived behavior control, behavior intention and situational factors. In this study, participants (N = 541) completed a questionnaire assessing their behavior of participation in the industrial colleges, which was analyzed by structural equation model (SEM). The results show that perceived needs, mandatory norms, exemplary norms, and self-efficacy have a significant positive effect on college students' intention to participate in industrial colleges. Behavior intention and self-efficacy have a significant positive effect on college students' participation in industrial colleges. Behavior intention plays a complete intermediary role between perceived needs and behavior, as well as between exemplary norms and behavior. Behavior intention plays a partial intermediary role between mandatory norms and behavior, as well as between self-efficacy and behavior. In addition, school support has a significant positive regulatory effect on college students' intention and behavior to participate in industrial colleges. These findings not only expand the relevant literature on college students' learning behavior, but also provide useful enlightenment for college education managers on how to stimulate college students' endogenous motivation to participate in industrial colleges.